Effects of panterritorial pricing policy for maize in Tanzania. - Suzuki, Yuriko; Bernard, Andrew (International Food Policy Research Institute, 1987)
It is widely believed that public parastatals in food grain markets of Africa in general, and East Africa in particular, have been a major source of price distortion and production imbalance. On the other hand, such parastatals have widely persisted in African foodgrain markets for reasons that are at least partly related to infrastructural backwardness. This paper by Yurido Suzuki and Andrew Bernard highlights these issues in the context of Tanzania. It complements other studies on similar issues in Africa conducted at IFPRI by Ulrich Koester (Regional Cooperation to Improve Food Security in Southern and Eastern African Countires, Research Report 64), Raisuddin Ahmed and Narendra Rustagi on agricultural marketing and rpice incentives, and by Christopher Delgado and Thomas Reardon on coarse grains in West Africa